On the margins: the challenges of identifying domestic violence in mental health services : findings of a qualitative Irish study - Donnelly, Elaine (Journal of family violence, 2021)
Although the relationship between mental ill health and the experience of domestic violence (DV) is well established, service users frequently report an absence of appropriate professional responses to disclosures. This study explored how professionals in an Irish mental health (MH) setting understand, identify and respond to DV in a multidisciplinary practice context. An exploratory qualitative approach using semi structured focus group interviews was employed. The data consisted of six focus group interviews with occupational therapists, nurses, consultant psychiatrists, junior doctors, social workers and psychologists working in acute MH care (n-27) in Ireland in 2018. Data was analyzed using Braun and Clarke’s Qualitative research in psychology, 3(2), 77-101, Braun and Clarke (2006) six stages of thematic analysis. Study findings suggest that a prevailing medical model along with an exclusive focus on physical forms of violence shaped the [in]visibility of the DV in this practice setting. DV issues were marginalized from MH care due to its construction as a social problem, with resultant patient needs related to DV not considered within the remit of MH services. This disconnected construction was influenced by several factors including training and education, fear, professional roles and team working in a dominant medical model. This study supports the need for conceptual frameworks that do not marginalize issues of DV in the discourse of MH care delivery but provide a foundation for service user centered collaboration across professional disciplines. The potential benefits of trauma informed care models in increasing recognition and response to DV in MH services are indicated by the present study.